2017
DOI: 10.1021/acs.jpclett.7b02480
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Assisted Quantum Coherence in Photosynthetic Complex

Abstract: Recent experiments [ Engel et al. Nature, 2007, 446, 782-786 ] revealed the existence of surprisingly long-lived quantum coherence in the noisy biological environment of the photosynthetic Fenna-Matthews-Olson (FMO) complex. Such coherence can clearly play an important role in facilitating efficient energy transfer. The occurrence of quantum coherence in quantum transport is also implicated in excitation transport processes in conjugated polymers [ Collini et al. Science, 2009, 323, 369-373 ]. Even though thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…We conjecture (and leave the verification to future studies) that these features persist beyond the Markovian limit, as steady-state currents should only be weakly affected by non-Markovianity. [49][50][51] The question still remains, why does ENAQT only appear in non-symmetric networks, which do not posses an inversion symmetry. In the presence of an inversion symmetry (which includes, as mentioned above, interchanging the source and drain terms), the master equation for inversion points (points connected by inversion, except for the source and drain sites) are exactly the same.…”
Section: And the Dephasing Part Of The Lindbladian Ismentioning
confidence: 99%
See 1 more Smart Citation
“…We conjecture (and leave the verification to future studies) that these features persist beyond the Markovian limit, as steady-state currents should only be weakly affected by non-Markovianity. [49][50][51] The question still remains, why does ENAQT only appear in non-symmetric networks, which do not posses an inversion symmetry. In the presence of an inversion symmetry (which includes, as mentioned above, interchanging the source and drain terms), the master equation for inversion points (points connected by inversion, except for the source and drain sites) are exactly the same.…”
Section: And the Dephasing Part Of The Lindbladian Ismentioning
confidence: 99%
“…In both cases we found the same results, namely, that nonsymmetric networks exhibit ENAQT, and that the behavior of the current correlates with Δ n , thus supporting our claims (details and results of these calculations are in the SI). We conjecture (and leave the verification to future studies) that these features persist beyond the Markovian limit, as steady-state currents should only be weakly affected by non-Markovianity. …”
mentioning
confidence: 90%
“…Reports of coherent beatings in complex systems continue to attract researchers because they suggest a mechanism for tuning photoinduced reactions, e.g., energy transfer, where possible implications have not previously been deeply considered . Coherence therefore has become an engaging topic in recent years. Theoretical studies have now predicted that coherent oscillations observed in many ultrafast experiments on light-harvesting complexes are assigned to vibronic coherence–quantum mechanical excitation delocalization that depends on the nuclear coordinates of the light-harvesting chromophores. This means that the vibrational motion of the chromophores involved becomes correlated by electronic coupling; therefore, the ladders of states of the chromophores do not independently absorb or emit energy. Thus, in many cases, the long-lived coherent oscillations observed in light-harvesting complexes (and charge separation) can be explained by exciton–vibration resonance.…”
mentioning
confidence: 99%
“…The environment of the light-harvesting protein has been modeled in different ways, including random telegraph noise (RTN) [4,5,6,7,8,9,10,11], the Haken-Strobl-Reineker (HSR) model [12,13,14,15,16] and collections of harmonic oscillators [2,17,18,19,20,21,3,22,23]. Earlier results show that the quantum transport efficiency may be enhanced for certain values of the parameters of the noise, such as dephasing rate [17,1,18,19,20,3,4,21,5,22,11], noise amplitude [6,14,15,8,9], reorganization energy [17,18,12,5,23], and noise correlations [2,13,7,16,24].…”
Section: Introductionmentioning
confidence: 99%